Protein Tyrosine Kinase Involvement in Learning-Produced Changes in Hermissenda Type B Photoreceptors - Jin, Iksung (American Physiological Society, 2009)
Learning-correlated changes in the excitability and photoresponses of Hermissenda's ocular type B photoreceptors are mediated by reductions in two distinct K(+) currents, I(A) and I(K-Ca). The suppression of these K(+) currents has been linked to conditioning-produced activation of protein kinase C (PKC). The question of whether PKC accounts completely for the changes in excitability and K(+) currents or whether other kinase(s) are involved has received little attention. In the present experiments, we asked whether protein tyrosine kinases (PTKs) might also contribute to conditioning-produced alterations in B cells. We found that the PTK inhibitors genistein and lavendustin A greatly reduced cumulative depolarization of type B cells, a short-term correlate of associative learning. This disruption occurred even when PKC activation had been either occluded by preexposure of type B cells to a phorbol ester or otherwise prevented by the pseudosubstrate inhibitor peptide PKC[19–31]. PTK inhibitors also increased the amplitude of the transient (I(A)) and delayed (I(Delayed)) components of voltage-dependent K(+) current that have previously been shown to be selectively reduced by conditioning and to contribute to cumulative depolarization. Genistein partially prevented the reduction of I(A) and I(Delayed) due to in vitro conditioning and blocked the changes in their voltage dependencies. Ionophoresis of pervanadate ion, a potent inhibitor of protein tyrosine phosphatases, depolarized type B photoreceptors and occluded conditioning-produced cumulative depolarization. Pervanadate also suppressed I(A) and I(Delayed), reduced their voltage dependence, and altered inactivation kinetics for I(A), mimicking conditioning. Western blot analysis using a phosphotyrosine antibody indicated that conditioning increased the phosphotyrosine content of many proteins within the Hermissenda CNS. Collectively, our results suggest that in addition to PKC, one or more PTKs play an important role in conditioning-produced changes in type B cell excitability. PTKs and PKCs converge to effect reductions in B cell K(+) currents during conditioning, apparently through distinct biophysical mechanisms.